THREE-DIMENSIONAL SYSTEM FOR ESTIMATING EFFICIENCY AND AGREEMENT OF ENTREPRENEURIAL ACTIVITY PRIORITIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the methodology for developing a strategy for improving the business entities performance in a transformation of the market environment, their factors, analyzed the main modern developing concepts a strategy for improving the entrepreneurial structures performance, in accordance with which, areas have been identified where the state can actively influence the healthy competition supporting process in the economy. Considerable attention is paid in the article to the issue of the business structures effectiveness.